Pengaruh Kinerja Keuangan Dan Pertumbuhan Perusahaan Terhadap Kondisi Financial Distress (Studi Pada Perusahaan Tekstil Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016) - Dea Sanchiani; Yustrida Bernawati (Jurnal Manajemen dan Bisnis Indonesia, 2018)
Financial distress is a condition where a company experiences financial difficulties which results in the company not being able to fulfill its liabilities. Such conditions will disrupt the operational activities of the company so that the net income becomes not maximal or even negative. This study aims to determine the effect of financial performance and company growth on financial distress. The study population were textile and garment companies listed on the Indonesia Stock Exchange (BEI) for the period 2012 to 2016, the manufacturing sub-sector with a total sample of 85 samples. The sampling technique used is saturated samples where all members of the population are used as samples. The analysis technique used is the method of logistic regression analysis with the help of SPSS Version 21. The results of this study indicate that profitability and leverage affect financial distress, while liquidity, activity, and company growth do not affect financial distress. Keywords : financial distress, liquidity, profitability, activity, leverage, sales growth